2015
DOI: 10.1007/978-3-319-23327-7_66
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Liquid Sample Handling Robot for High-Throughput Fourier Transform Infrared Spectroscopy

Abstract: The identification of food spoilage moulds and other microorganisms by using Fourier Transform Infrared (FTIR) spectroscopy is too slow for food industries and laboratories nowadays because of the manual inspection and highly professional needed. While this approach is suitable for small sample numbers, dealing with a large quantity of specimens require FTIR sample preparation to be carried out by a robotic system to increase the throughput but also to avoid cross-contamination. This paper presents a novel mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Combined with the Duetz microtiter plate system (Duetz-MTPS), FTIR can serve as a rapid tool for monitoring of high throughput studies, such as screening of fungal strains for high and low value lipid production [10,70]. Moreover, high throughput screening was strengthen by a fully automated set-up of the biomass samples preparation for the FTIR-HTS analysis [71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the Duetz microtiter plate system (Duetz-MTPS), FTIR can serve as a rapid tool for monitoring of high throughput studies, such as screening of fungal strains for high and low value lipid production [10,70]. Moreover, high throughput screening was strengthen by a fully automated set-up of the biomass samples preparation for the FTIR-HTS analysis [71][72][73].…”
Section: Introductionmentioning
confidence: 99%
“…2100 cm −1 , could be utilized in peak normalization preprocessing [ 39 ]. In addition, we can expect that the use of a robotic system for sample preparation on silicone plates could increase the precision of HTS–FTIR measurement [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that HTS FTIR spectroscopic analysis of lipids in cell biomass correlates very well with GC analysis, and can be used for the prediction of total lipid and several groups of fatty acids (saturated, monounsaturated, and polyunsaturated) in fungal cell biomass [ 7 ]. Analogous to Duetz MTPS, HTS FTIR features microplate design well suited for automation systems [ 31 ], thus it is far more suitable for high-throughput screening than probe- or cell-based ATR FTIR setting. In the present study we evaluate HTS FTIR spectroscopy as a unified method for simultaneous quantification of both intra- and extra-cellular metabolites, as well as substrate consumption in high-throughput screening of microbial bioprocesses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the heterotrophic microalga C. cohnii reached a significantly higher biomass and lipid concentration in the MTPS than in the 1.5 L bioreactor, probably due to shear force sensitivity of this species. It is worth mentioning that the screening throughput of oleaginous microorganisms in the Duetz-MTPS can be increased by combining at-line FTIR spectroscopy and the automation of the cultivation-analytical system (Li et al 2016 ). Reproducibility and scalability results demonstrated that the Duetz-MTPS can be used for the cost-efficient, high-throughput screening of both single-cell and multicellular oleaginous microorganisms.…”
Section: Discussionmentioning
confidence: 99%